Sonochemical Synthesis of 2'-Hydroxy-Chalcone Derivatives with Potential Anti-Oomycete Activity - Génesis López; Marco Mellado; Enrique Werner; Bastián Said; Patricio Godoy; Nelson Caro; Ximena Besoain; Iván Montenegro; Alejandro Madrid (MDPI AG, 2020)
This work reports on the synthesis of eight new 2'-hydroxy-chalcones with potential anti-phytopathogenic applications in agroindustry, AMONG others, via Claisen-Schmidt condensation and ultrasound assisted reaction. Assays showed three chalcones with allyl moieties strongly inhibited growth of phytopathogenic oomycete Phytophthora infestans; moreover, compound 8a had a half maximal effective concentration (EC50) value (32.5 µg/mL) similar to that of metalaxyl (28.6 µg/mL). A software-aided quantitative structure-activity relationship (QSAR) analysis of the whole series suggests that the structural features of these new chalcones-namely, the fluoride, hydroxyl, and amine groups over the carbon 3' of the chalcone skeleton-increase anti-oomycete activity.